Foreign and Domestic Online Media Representation of Indonesian Minister of Finance: A Feminist Stylistics Approach - Novra Melisa P. Hutabarat; Rahmadsyah Rangkuti; Sharon Dinda N. Hutabarat (Dinasti Publisher, 2025)
An analysis of how a well-known female public person is portrayed in international and local web media, with a focus on gender representation. The study clarifies the significance of impartial and fair coverage of female leaders in the media by using a feminist stylistics approach. This can help to promote gender equality in society and destroy gender stereotypes. Using a qualitative approach, this study investigates how gender relations are portrayed at the word, phrase/sentence, and discourse levels utilizing feminist stylistics framework developed by Sara Mills. The results show that cultural norms and Sri Mulyani's standing both domestically and globally have an impact on how the Indonesian Minister of Finance is portrayed on foreign and domestic news websites. These factors produce discrete but diverse outcomes. The study finds that the minister is treated properly and without overt gender prejudice by utilizing the feminist stylistics theory framework's three levels of analysis. The results show that cultural norms and Sri Mulyani's standing both domestically and globally have an impact on how the Indonesian Minister of Finance is portrayed on foreign and domestic news websites. These factors produce discrete but diverse outcomes. The study finds that the minister is treated properly and without overt gender prejudice by utilizing the feminist stylistics theory framework's three levels of analysis. This study uses a feminist stylistics method to analyze how Indonesia's Minister of Finance is portrayed in the media, highlighting the significance of impartial and fair representation of public leaders. This thorough examination advances our knowledge of how gender is portrayed in the media and emphasizes the significance of speaking with public personalities in an impartial and fair way.